(untitled) (National Administration Journal, 2020)
The purpose of this work is to analyze the kinds of human talent practices that have a positive relation on commitment management based on the study case of a technological company in Quito, Ecuador. A questionnaire was used as an instrument to gather information and make a correlational analysis to answer the research question. The results enable to identify the factors that have a direct and positive influence on the collaborators’ commitment to the organization and its objectives while evidencing the influence of human talent management as a strategic component.